The Design of Real-Time Location Detection Application on Android for Trans Musi to Help the Use of Trans Musi Bus in Palembang City - Salsabila, Salma; Ramadhan, M. Ridho; Ghiffari Iskandar, Muhammad Naufal; Dwijayanti, Suci (Multidisciplinary Applied Research and Innovation, 2021)
Trans Musi is a public transportation used by numerous people in Palembang because of its facilities and the affordable cost. It spreads across all points of the city and provides conveniences, such as bus stop and transit stop for the passengers while waiting for the bus. However, bus rapid transit (BRT) system of Trans Musi still has several obstacles in its implementation, caused in inefficient services, especially in providing real-time position information through applications. Nevertheless, the application that has been developed only allowed users to get information on the nearest bus stop, while information about bus position was unknown and not real-time. Thus, this study addressed this problem by making a Trans Musi Location Detector application design which is integrated with a location detection device of which aims to display real-time information, such as coordinates, speed, time, and route. The methodology used in this study was simulation approach to show how the system works. This application purposes to help users to use Trans Musi, such as accessing the latest bus locations, determining the nearest bus stop, as well as the arrival and departure times of buses at the nearest bus stop. In addition, this application is supported by hardware to obtain accurate information sent to the application. The hardware consists of an electrical box with the main component of a global positioning system which is placed on the bus dashboard, and a Radio-frequency identification (RFID) box which is placed at each bus stop. Besides giving information of bus positions in real-time, this application also has a feature to support the government in implementing health protocols related to physical distancing on public transportation during the COVID-19 pandemic. Such feature provides a full passengers indicator by giving notification of number of passengers on the bus to fulfill the physical distancing criteria.